PELATIHAN PEMANFAATAN TIKTOK SEBAGAI UPAYA PENINGKATAN PEREKONOMIAN ANAK MARJINAL LEMBAGA PPAP SEROJA SURAKARTA - Wahyuni, Dian; Ayu Azhari, Wulan; Khifata A'yun, Arina; Audi Rachmawati, Zahra; Fuad Hidayat, Marwan; Handini, Oktiana (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
Marginalized children in the Seroja Surakarta Women and Children Empowerment Institution (PPAP) have a background of various factors, including poverty, difficulty getting a job, no longer having parents or disabled, no place to live, and low education. Seeing these problems, what is needed by marginalized children is how they can get welfare in the present and in the future, especially in the economic aspect. Therefore the Slamet Riyadi University PKM Team carried out training activities on using the Tiktok application to help these marginalized children to be able to work even if they only used cellphones. Marginalized children will be given knowledge about using the Tiktok application, training to become Tiktok Sellers, namely how they can have an online shop on Tiktok, Host Live Tiktok Shops, namely how they can do live, sell, and Tiktok Affiliate so they can get sales commissions without the need to have prior capital. With this training, children can work even if only at home.